Mass School Shootings and the Short-Run Impacts on Use of School Security Measures and Practices: National Evidence from the Columbine Tragedy. (2nd January 2020) - Curran, F. Chris; Fisher, Benjamin W.; Viano, Samantha L.
ABSTRACT: Following high-profile school shootings, policymakers and educators seek ways to prevent such shootings, but there has been little research on school-level responses in the immediate aftermath of such events. This study examines how school-level security measures and practices changed after the 1999 Columbine shooting using a nationally representative sample of elementary school principals from the Early Childhood Longitudinal Study ( N = 810). Exploiting variation in the timing of survey completion relative to the Columbine shooting, we used regression analysis to examine the use of seven security measures and practices before and after Columbine. Elementary schools were 16 percentage points more likely to lock exits after Columbine and, over time, were more likely to use visitor sign in procedures. School racial/ethnic composition had a moderating effect in some models. Implications for policy and schools are discussed.